Study on the economic benefits of carbon-neutral digital platforms for sustainable development based on the GPT-QRCNN model - Yang, Huifang; Zhou, Xiang (Frontiers in Ecology and Evolution, 2023)
A carbon-neutral digital platform is an economic model that promotes sustainable development by reducing carbon emissions through digital technology and data platforms. In order to assess the economic benefits of carbon-neutral digital platforms, this article proposes a method based on the GPT-QRCNN model. This method combines the GPT and QRCNN models to accurately predict and analyze the economic benefits of carbon-neutral digital platforms. The method first uses the GPT model to extract features of platform data, and then combines it with the QRCNN model for sequence modeling to improve the model's prediction accuracy and generalization ability. At the same time, actual platform data is used for experimental verification in this article.The experimental results demonstrate the practical significance and application value of the method proposed in this paper in evaluating the economic benefits of carbon-neutral digital platforms.